Vaginal epithelioid angiosarcoma: A literature review of a rare entity in an unusual site - J. Weishaupt; J. Miller; M.K. Oehler (Elsevier, 2021)
We describe an extremely rare case of a 66-year-old woman with a vaginal epithelioid angiosarcoma. She presented with constitutional symptoms, pelvic pain, vaginal bleeding, and a violaceous vaginal lesion. A thorough gynaecological examination, tissue biopsy and imaging were crucial to establish an accurate diagnosis. With only 3 other cases reported in the literature, epithelioid angiosarcoma of the vagina seem to present late due to their nonspecific presentation and secluded location. Once diagnosed, optimal treatment is difficult to determine and together with the overly aggressive behaviour of these tumours, they are associated with a poor prognosis. To our knowledge, our case study and systematic literature review is the first to compare the management outcomes of epithelioid subtype angiosarcomas of the vagina. The rarity of this pathology contributes to diagnostic difficulties and lack of consensus regarding treatment of angiosarcomas of the vagina.